Childhood amblyopia in a tertiary eye care center in western India - Jai A. Kelkar; Harsh H. Jain; Aditya S. Kelkar; Shreekant Kelkar (International Journal of Ophthalmology)
AIM: To describe the demographics, clinical characteristics and treatment outcomes of childhood amblyopia in a tertiary eye center in western India. METHODS: This was a retrospective longitudinal hospital-based study of 1382 children aged ≤12y included in the National Institute of OphthalMology AmBlyopia StUdy in Indian Paediatric EyeS (NIMBUS) Study. Data on patient demographics, treatment approach, and best-corrected visual acuity (BCVA) changes were reviewed. RESULTS: The mean age of the study cohort was 4.54±2.46y, with males constituting the majority (55.4%). The cause of amblyopia was refractive error in 73.2%, strabismus in 7.3%, and anisometropia in 6.8% of eyes. The majority of therapies comprised glasses (74.4%), followed by occlusion+glasses (10.3%), occlusion alone (7.3%), and surgery+patching+glasses (5.1%). The mean occlusion time was 2.46±1.14h. After a median follow-up of 10.00 (6–85)mo, the mean BCVA significantly improved from 0.85±0.41 to 0.55±0.42 logMAR. Subgroup analysis revealed BCVA gain for all etiologies, including refractive errors (P<0.001), strabismus (P<0.001), cataract (P<0.001), and ptosis (P<0.001). Additionally, eyes with refractive errors showed significantly better BCVA than eyes with cataracts (P<0.001), strabismus (P<0.001) and marginally better BCVA than eyes with ptosis (P<0.05), both at the baseline and final visit. CONCLUSION: Refractive errors are the commonest cause of amblyopia, followed by strabismus and anisometropia. Timely detection, optimal therapy, and periodic follow-up are crucial in bettering visual acuity regardless of the cause.